PROTOTYPE SISTEM PAKAR GANGGUAN MENSTRUASI MENGUNAKAN METODE FORWARD CHAINING (STUDI KASUS : RS. KAMBANG KOTA JAMBI): EXPERT SYSTEMS, MENSTRUAL DISORDERS, MYSQL, PHP, EXPERT SYSTEMS, WEB ME - Adhiatma, Novri; Ikhsan, Muhammad; Hidasari S, Ria (LP2M STMIK Nurdin Hamzah Jambi, 2019)
At first this Kambang Hospital was a Joint Practice Specialist. Then it turned into the Kambang Clinic, which had been introduced and turned into Kambang Hospital. At the Kambang Hospital an examination of the diagnosis of menstrual disorders is still using the manual system using a blood test, urine test and further examination with the doctor in question. The purpose of this study was to design an expert system to diagnose menstrual disorders by applying the Forward Chaining Method. The system that will be designed is a system that transfers the knowledge of a doctor to an expert system (Artificial Intelligence), which will help patients know about their illness. This system is designed based on a website using the PHP Framework Code Igniter script and uses a MySQL database. With the existence of this Menstrual Disorders Expert System built, it makes it easier for the general public to diagnose menstrual disorders from an early age, by inputting data on types of disorders, symptoms, rules, and asking us to produce output in the form of checking reports and patient reports.